Strategi Kepala Sekolah Dalam Meningkatkan Profesionalisme Guru - Ari Wibowo; Achadi Budi Santosa santosa (UIR Press, 2022)
The success of education cannot be separated from the efforts of the principal as a leader in directing and motivating teachers. This study aims to reveal the principal's leadership strategy in improving teacher professionalism. This study uses a descriptive qualitative approach, data sources include all teachers and vice principals, while data collection is through interview and documentation techniques. The analysis uses continuous participatory techniques, through the stages of data collection, reduction, presentation, and drawing conclusions. The results showed that the principal's strategy in increasing teacher professionalism was by activating the teacher working group (KKG), motivating teachers, training, comparative studies, teacher evaluation meetings, classroom supervision, giving punishment and rewards, and through a participatory leadership style.